Poetry of the revolution : Marx, manifestos, and the avant-gardes - Puchner, Martin, 1969- (Translation/transnation., 2006)
Martin Puchner tells the story of political and artistic upheavals through the political manifestos of the 19th and 20th centuries. He argues that the manifesto was the genre through which modern culture articulated its revolutionary ambitions and desires.